2017
DOI: 10.1017/s1751731116002573
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour and welfare of sows and piglets in farrowing crates or lactation pens

Abstract: Temporary confinement during parturition and early postpartum may provide an intermediary step preceding loose housing that offers improvement in sow and piglet welfare. Three experiments were conducted to investigate the implications of replacing farrowing crates (FCs) with an alternative housing system from 3 days postpartum until weaning. In each experiment sows farrowed in FCs and were randomly allocated at day 3 of lactation to either a FC or a pen with increased floor space (lactation pen (LP)) until wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 30 publications
3
61
0
2
Order By: Relevance
“…The numerically higher piglet total mortality in the free farrowing pens compared with the farrowing crate pens indicating a potential big financial loss in the industry [20]. However, Singh et al [21] found no difference in piglet mortality between traditional farrowing crate pens and free farrowing pens from day 3 of lactation until weaning based on the recording of 672 litters in total. With the banning of the farrowing crate in several countries, more information was collected in practice with a promising result of similar total piglet mortality between non-confined and crate farrowing systems (in Switzerland, loose = 17.2% from 18824 litters and crates = 18.1% from 44837 litters) [2,22].…”
Section: Discussionmentioning
confidence: 99%
“…The numerically higher piglet total mortality in the free farrowing pens compared with the farrowing crate pens indicating a potential big financial loss in the industry [20]. However, Singh et al [21] found no difference in piglet mortality between traditional farrowing crate pens and free farrowing pens from day 3 of lactation until weaning based on the recording of 672 litters in total. With the banning of the farrowing crate in several countries, more information was collected in practice with a promising result of similar total piglet mortality between non-confined and crate farrowing systems (in Switzerland, loose = 17.2% from 18824 litters and crates = 18.1% from 44837 litters) [2,22].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for this practice is to improve piglet survival rate by protecting newborn piglets from fatal or injurious crushing by the mother sow [1]. However, the confinement of sows in crates has a negative impact on the sows' welfare, such as limited freedom of movement, limited social interactions with newborn piglets [2,3], and diminished health [4,5]. Confinement also prevents much of the prenatal nest-building behaviour, an essential part of the behavioural repertoire in sows, which starts approximately 24 h before parturition, is most intense 6 to 12 h before parturition, and then, decreases as parturition begins [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Duve et al, 2012;Held an Jensen et al, 1998;marmosetcare.com, 2017;Miguel-Pacheco et al, 2015); positive emotions or positive affective states (e.g. Clegg and Butterworth, 2017;Green and Mellor, 2011;Lampe et al, 2017;Mellor, 2012;Minero et al, 2016;Rushen and de Passillé, 2012;Singh et al, 2017); a -(e.g. Lawrence, 1987); or that animals are (Wemelsfelder and Farish, 2004).…”
mentioning
confidence: 99%